2019
DOI: 10.3390/mi10070450
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bacteriophages with Insulator-Based Dielectrophoresis

Abstract: Bacterial viruses or phages have great potential in the medical and agricultural fields as alternatives to antibiotics to control nuisance populations of pathogenic bacteria. However, current analysis and purification protocols for phages tend to be resource intensive and have numbers of limitations, such as impacting phage viability. The present study explores the potential of employing the electrokinetic technique of insulator-based dielectrophoresis (iDEP) for virus assessment, separation and enrichment. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
(59 reference statements)
0
42
0
Order By: Relevance
“…Currently, the most recent report on iDEP based virus manipulation is the work of Adriana et al [ 104 ] who assessed bacterial virus (phage) separation and enrichment with iDEP traps ( Figure 5 ) on structurally and inherently distinct, phages of P. chlororaphis phage 201ϕ2-1, P. aeruginosa phage ϕKZ, S. enterica phage SPN3US, and it was determined that the virion trapping occurred at lower voltages in devices with circular insulating posts compared to oval-shaped ones ( Figure 5 d) since these generate lower DEP forces than the latter. The results indicated that virus behavior in the iDEP system could be predicted based on the trapping response of the phage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, the most recent report on iDEP based virus manipulation is the work of Adriana et al [ 104 ] who assessed bacterial virus (phage) separation and enrichment with iDEP traps ( Figure 5 ) on structurally and inherently distinct, phages of P. chlororaphis phage 201ϕ2-1, P. aeruginosa phage ϕKZ, S. enterica phage SPN3US, and it was determined that the virion trapping occurred at lower voltages in devices with circular insulating posts compared to oval-shaped ones ( Figure 5 d) since these generate lower DEP forces than the latter. The results indicated that virus behavior in the iDEP system could be predicted based on the trapping response of the phage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, iDEP is actively being investigated to manipulate various types of viruses and develop innovative high throughput diagnostic devices due to the selective nature of applied trapping voltages on viruses. The findings encountered by Adriana et al [ 104 ] shed light on one such application of iDEP for analyses and separation of phage mixtures. Tables S3 and S4 (Supplementary Materials) further highlight iDEP publications and device patents on various virus manipulation work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DEP is applied, for instance, to control particles and detect cancer cells from the blood [14]. DEP is greatly used in biological applications for the separation of virus particles [15,16], the separation of nanoparticles [17], droplet manipulation [18], and trapping and manipulation of single cells and particles [19]. Dielectrophoresis (DEP) and alternating current electrothermal (ACET) flow are also combined to realize continuous particle trapping, switching, and sorting [20].…”
Section: Introductionmentioning
confidence: 99%